Baby geniuses and the treasures of Egypt [videorecording (DVD)] - Voight, Jon; Paul, Steven; McNamara, Shawn (SP Entertainment, 2014)
Talking baby detectives travel to Egypt to track down a baby villain and put him in "time-out."